2010
DOI: 10.1093/cercor/bhp282
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Development in Adolescence: A DTI Study

Abstract: Adolescence is a unique period of physical and cognitive development that includes concurrent pubertal changes and sex-based vulnerabilities. While diffusion tensor imaging (DTI) studies show white matter maturation throughout the lifespan, the state of white matter integrity specific to adolescence is not well understood as are the contributions of puberty and sex. We performed whole-brain DTI studies of 114 children, adolescents, and adults to identify age-related changes in white matter integrity that chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
442
3
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(488 citation statements)
references
References 108 publications
37
442
3
6
Order By: Relevance
“…They are also consistent with activation studies using functional MRI, which have reported greater interhemispheric activation in females on a language task, in which they excelled (44), and greater focal intrahemispheric activation in males on a spatial task, in which they excelled (45). With respect to development, DTI studies (23,24) have shown higher FA and lower MD in the CC in females during midadolescence, confirming a similar trend in our data. Although FA and MD provide measures of WM integrity, connectomic studies like ours are required to complete the picture of connection-wise systems.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They are also consistent with activation studies using functional MRI, which have reported greater interhemispheric activation in females on a language task, in which they excelled (44), and greater focal intrahemispheric activation in males on a spatial task, in which they excelled (45). With respect to development, DTI studies (23,24) have shown higher FA and lower MD in the CC in females during midadolescence, confirming a similar trend in our data. Although FA and MD provide measures of WM integrity, connectomic studies like ours are required to complete the picture of connection-wise systems.…”
Section: Discussionsupporting
confidence: 92%
“…Examination of DTI-based scalar measures (16) of fractional anisotropy (FA) and mean diffusivity (MD) has demonstrated diverse outcomes that include increased FA and decreased MD in males in major WM regions (17)(18)(19), higher CC-specific FA in females (20,21), and lower axial and radial diffusivity measures (22) in males. Throughout the developmental period, females displayed higher FA and lower MD in the midadolescent age (12-14 y) (23), and this result was established on a larger sample size (114 subjects) as well (24). On the other hand, sex differences on the entire age range (childhood to old age) demonstrated higher FA and lower MD in males (19,25,26).…”
mentioning
confidence: 77%
“…Our findings regarding functional connectivity may also be explained by neural maturation. As diffusion becomes more restricted with age in frontal pathways (Asato, Terwilliger, Woo, & Luna, 2010; Liston et al., 2006), functional connectivity patterns may become more consistent across different cognitive tasks, as suggested by the current study. In order to further explore the relationship between age‐related morphological reorganization and neural recruitment, future studies should directly compare measures of cortical activity and connectivity with indices of anatomical neural maturation (e.g., cortical thinning and axonal myelination).…”
Section: Discussionmentioning
confidence: 99%
“…As an insulator on certain axons, myelin increases the speed of signal impulses via saltatory conduction. WM functions to connect areas of GM and sends these signals to a variety of regions including the brainstem and limbic system [1]. These signals are used as the nervous system's communication, and can be translated into cognitive functioning processes or motor processes [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, increases in GM volumes peak well before an individual's 20's, whereas increases in WM volume peaks in middle age [18,31]. In general, WM has been determined to increase significantly during adolescence [1,15,18,21,25,26,28] yet decreases in later adolescent stages [13,15,26,29]. There is also evidence to suggest that WM develops differently between males and females; men have a parallel rate of growth in both GM and WM to cranial volume, whereas women increase in WM at a slower rate in relation to cranial volume [3,9,11,13,35].…”
mentioning
confidence: 99%